Elevated Carbohydrate Antigen 19-9 in Patients with True (Epithelial) Splenic Cysts – Rare or Undiscovered? - Michal Soudack; Alon Ben-Nun; Chaim Toledano (Canadian Journal of Gastroenterology)
Carbohydrate antigen 19-9 is a well known marker for pancreatic adenocarcinoma. However, its limitation is its nonspecificity, because elevated levels may be encountered in other gastrointestinal disorders, both benign and malignant. The following case is a patient with a true (epithelial) splenic cyst with elevated serum levels of carbohydrate antigen 19-9.